(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2023)
This contribution will examine different communicative and narrative strategies adopted by some documentary productions in order to visualize something invisible, like the virus and its effects. Through the case studies I will take into account, my intent is to reflect upon the pandemic narration, which replaces or alternates the photographic realism of the images of pain and suffering, intended as scientific and incontrovertible proof of the virus manifestation, with a modernist narrative, mixing interviews with infographic material, maps, dashboards, photomicrographs, and computer graphics animations. Despite their profound mediation by software that makes pictures out of numbers, these informatic images, reported daily in news channels and broadcasts as well, besides shaping the relationships between scientific research, documentary, and its explanatory and pedagogical power to narrate, reconfigure the collective imagination of the pandemic in a bioinformation era.